1995
DOI: 10.1007/bf01719431
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dairy products on plasma uric acid in women

Abstract: Elevated levels of plasma uric acid have been linked to increased risk of cardiovascular diseases and their complications. As dairy proteins have been found to decrease plasma uric acid without increasing glomerular filtration rate, a sample of postmenopausal women living in Montreal was studied to investigate the nature of this relationship. Participants (158 Roman Catholic nuns) were randomly assigned to one of two test diets for a period of four weeks: the dairy foods group (n = 81) consumed approximately 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 16 publications
3
47
1
6
Order By: Relevance
“…Multivariate analysis revealed major inverse correlation only between skimmed milk intake (low fat yoghurt and not other dairy products) and the frequency of gout. It has been observed that milk protein intake, such as casein and lactalbumin that have uricosuric properties, reduce uricaemia levels in healthy subjects [10], whereas a four-week randomised trial of subjects on a dairy product-free diet significantly increased uricaemia levels [11]. According to Choi and coworkers [9], dairy products have a low purine content, thus milk proteins could reduce uricaemic without supplying the purine load contained in other proteins, such as meat and fish, even if the negative risk of elevated protein intake in kidney stone formation is common knowledge [12].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis revealed major inverse correlation only between skimmed milk intake (low fat yoghurt and not other dairy products) and the frequency of gout. It has been observed that milk protein intake, such as casein and lactalbumin that have uricosuric properties, reduce uricaemia levels in healthy subjects [10], whereas a four-week randomised trial of subjects on a dairy product-free diet significantly increased uricaemia levels [11]. According to Choi and coworkers [9], dairy products have a low purine content, thus milk proteins could reduce uricaemic without supplying the purine load contained in other proteins, such as meat and fish, even if the negative risk of elevated protein intake in kidney stone formation is common knowledge [12].…”
Section: Discussionmentioning
confidence: 99%
“…Остальные компоненты и объем пище-вого рациона были полностью идентичны. В группе на мо-лочной диете динамика уровня МК была статистически незначимой (отмечалось снижение на 4 мкмоль/л относи-тельно исходного содержания), но у пациентов на безмо-лочной диете он достоверно увеличился (на 7,8 мкмоль/л; р=0,03) [62]. Более детальный анализ данной статьи позво-ляет сделать еще несколько выводов.…”
Section: мясо и морепродук тыunclassified
“…Более детальный анализ данной статьи позво-ляет сделать еще несколько выводов. Так, включение в ра-цион молока хотя и привело к существенному увеличению потребления белка, но уменьшило долю белков животного происхождения, косвенно подтверждая правоту тех иссле-дователей, которые не нашли зависимости между общим объемом потребления белка и гиперурикемией [62]. Одной из причин, которые могли уменьшить урат-снижающий эффект молока, могло быть параллельное увеличение по-требления молочных жиров, как сатурированных, так и не сатурированных, а также холестерина, способствующих кетонемии, при которой клиренс МК снижается [63].…”
Section: мясо и морепродук тыunclassified
See 1 more Smart Citation
“…One of these strategies, which has gained increasing attention in recent years, is the use of dairy-rich nonenergy-restricted diets [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The pioneering works by Zemel et al [10,25] in the early years of the last decade demonstrated that increasing dietary calcium intake, especially from dairy products, in the absence of energy restriction leads to a repartitioning of dietary energy from adipose tissue to lean body mass and consequently results in a net reduction in body fat mass and weight gain in both mice and humans.…”
Section: Introductionmentioning
confidence: 99%